Environmental Conditions and Grazing Exerted Effects on Arbuscular Mycorrhizal in Plants at Southern Patagonia Rangelands - Toledo, Santiago (2022)
Arbuscular mycorrhizal (AM) fungi play a major role in maintaining ecosystem functions. AM fungi are found in most ecosystems including rangelands currently under increasing pressures from human activities. Southern Patagonia (Argentina) is a semiarid region influenced by extensive livestock production in rangelands. There is a lack of information about the environmental conditions and functionality of AM fungi in plant species of Patagonia ecosystems associated with livestock grazing. We assessed how soil properties, climatic conditions, and grazing intensities influence the response of AM fungi colonization. We studied most palatable and representative plant species (Poa dusenii, Rytidosperma virescens, Festuca gracillima, Nardophylum bryoides, Mulguraea tridens, and Carex argentina) growing in main ecological areas of Southern Patagonia. Most of the studied plant species (except C. argentina) presented AM symbiosis. AM colonization showed a negative relationship with soil organic carbon and nitrogen and a positive relationship with soil bulk density and pH. Results suggest that plants promoted a higher root AM colonization when soil nutrients and water availability (rainfall) are limiting. Sheep stocking rates had a differential impact depending on the ecological areas and plant life forms. High grazing decreased the AM colonization in the ecological areas with palatable plant dominance, suggesting that the impacts of grazing could lead to further negative effects on the ecosystem. Moderate grazing allows to maintain higher AM colonization, which would probably benefit the aboveground production of palatable plant and, consequently, to herbivores, particularly in degraded rangelands like Patagonian steppes. This study improves the knowledge of AM association in Patagonian semiarid rangelands by increasing our understanding of the impacts of grazing on belowground ecology. This information becomes relevant for grazing sustainable management, which may contribute to food security.